Cold snare endoscopic mucosal resection versus standard hot technique for large flat nonpedunculated colonic lesions: a randomized controlled trial - Nogales, Oscar; Carbonell Blanco, Carlos; Montori Pina, Sheyla; Pellisé, María; Martínez Sempere, Juan F.; Riu Pons, Fausto; Mangas-Sanjuan, Carolina; Daca-Alvarez, María; Uchima, Hugo; Aranda-Hernández, Javier; Alvarez Delgado, Alberto; Rodríguez de Santiago, Enrique; Santiago García, Jose; Cañete Ruiz, Ángel; Miranda García, Pablo; Núñez Rodriguez, Henar; Herreros-de-Tejada, Alberto; Valdivielso Cortazar, Eduardo; De María, Pedro; Busquets, David; Elosua, Alfonso; Rivero-Sánchez, Liseth; López-Ibáñez, María; Alvarez-Gonzalez, Marco A.; Albéniz, Eduardo; on behalf of the Mucosal Resection and Third-Space Endoscopy SEED Working Group (Endoscopy, 2025)
Backgrounds Cold snare EMR (CS-EMR) in large flat nonpedunculated colonic lesions (LFNPCLs) is an alternative to the standard EMR procedure with a better safety profile, but scientific evidence on its efficacy is unavailable. This study aimed to compare the recurrence rate between the two techniques at 6 months. Secondary aims were comparison of the safety profile and procedure-related outcomes.Methods This was a noninferiority, multicenter, open-label, randomized controlled trial of consecutive large (≥ 20 mm) LFNPCLs without suspicious features of submucosal invasion.Results 229 patients were randomized to receive CS-EMR (n = 115) or EMR (n = 114). The median lesion size was 25 mm and 74.6 % were adenomas. The trial was stopped early by clinical consensus according to a safety monitoring board. At first surveillance colonoscopy (n = 220) the recurrence rate was significantly greater in the CS-EMR group than in the EMR group: 33.0 % vs. 16.2 % (P = 0.004) and 34.7 % vs. 14.8 % (P = 0.001) in the intention-to-treat and per-protocol analyses, respectively. According to the subgroup analysis, the recurrence rate was significantly greater after CS-EMR for LFNPCLs ≥ 30 mm (43.1 % vs. 18.2 %). There was no difference in the rate of adverse events. The use of clips was more common in the EMR group (52.6 % vs. 27.8 %).Conclusions The recurrence rate of LFNPCLs after CS-EMR was significantly greater than after the standard hot technique. A similar safety profile was found between groups.